DEVELOPMENT AND EVALUATION OF NEW BADMINTON MODULE IN PHYSICAL EDUCATION - Nguang Ung Siong; Syed Kamaruzaman Bin Syed Ali (Journal of Islamic, Social, Economics and Development, 2023)
The new module developed for Badminton must go through a thorough evaluation process to determine the module's validity and reliability before it can be used by high school students in in physical education classes. This research aimed to evaluate a new Badminton module that includes aspects of Badminton skills, motivation and self-confidence. 7 experienced physical education and Sport Science experts were appointed to conduct an assessment to determine the validity of the constructed module. After evaluating the validity of the module, a pilot study involving high school students was conducted to determine the reliability of the module. The module validity results obtained from the experts’ assessment in this research shows that the content validity score is high, while the module reliability obtained from the pilot study also showed a great overall Cronbach Alpha score. Thus, the high validity and reliability results of this research indicate that the constructed module is appropriate for high school students and also has a high level of consistency. When this new module is used in Badminton learning sessions in Physical Education classes, it has a great potential of achieving targeted learning objectives. Therefore, it is proposed to conduct an experimental study to assess the impact of this module on high school students in Malaysia.